Evaluation of the technical and economic aspects of solar photovoltaic plants under different climate conditions and feed-in tariff - YILMAZ, MUSTAFA (My University, 2022)
© 2022 Elsevier LtdIn order to meet the energy demand and reduce the environmental pollution, it is necessary utilize photovoltaic (PV) module to produce electrical energy. There are many factors such as solar radiation, PV module material, wind energy, soiling factor, shading effect, geographical location, cell temperature is affecting the performance of the PV module. In this context, the performance of the multi crystalline based two PV plants has been examined. In this work, test is carried out in two solar plants installed at Kastoria, Greece (500kW, ground mounted) and Kocaeli, Turkey (110kW, roof mounted) and the results are compared with PVSYST software simulation results. From the results, it is found that the temperature losses for Kastoria and Kocaeli plants are obtained as 7.9% and 7.6% respectively. This leads to increase the performance ratio of 79% and 72.2% for Kastoria and Kocaeli plants respectively. Similarly, the maximum energy output is obtained for PVGIS database for all three models (Liu Jordan model, Hay Davies model and Perez model). The Internal Rate of Return for Kocaeli plant is 7.08% and for Kastoria plant is 6.71%. In addition, the Net Present Value for Kastoria and Kocaeli plant is obtained as 821900€ and 174072€ respectively.
Keywords: Makina Mühendisliği; Enerji; Güneş Enerjisi; Mühendislik ve Teknoloji; Mechanical Engineering; Energy; Solar energy; Engineering and Technology; Mühendislik, Bilişim ve Teknoloji (ENG); Mühendislik; MÜHENDİSLİK, MEKANİK; ENERJİ VE YAKITLAR; Engineering, Computing & Technology (ENG); ENGINEERING; ENGINEERING, MECHANICAL; ENERGY & FUELS; Energy Engineering and Power Technology; Automotive Engineering; Renewable Energy, Sustainability and the Environment; General Energy; Fuel Technology; Energy (miscellaneous); Computational Mechanics; Physical Sciences; Photovoltaic (PV) module; Soiling factor; Photovoltaic Geographical Information System (PVGIS); Photovoltaic System (PVSYST); PERFORMANCE ANALYSIS; IRRADIANCE COMPONENTS; INCLINED SURFACES; MODELS; SIMULATION; RADIATION; DIFFUSE; SYSTEMS; AREAS; PARK; Photovoltaic Geographical Information System (PVGIS)